2021
DOI: 10.1108/jima-08-2020-0240
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the comparative perception of e-payment: role of e-shopping value, e-payment benefits and Islamic compliance

Abstract: Purpose This study aims to examine three factors affecting the comparative e-payment perception, namely, perceived e-shopping value, e-payment benefits and Islamic Sharia compliance. It verifies an original model explaining the comparative perception of e-payment as a tool to pay online purchases. The newly integrated variables are the perceived compliance of the e-payment with Islamic Sharia, as a moderator, and the perceived e-shopping value, as a predictor. This investigation also tested the mediating role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
1
12
0
3
Order By: Relevance
“…Aji et al (2020) state that the riba' that may be contained in e-money can create individual disinterest in adopting e-money technology to become a major obstacle to creating a cashless society in Indonesia. However, an interesting finding is stated by Garrouch (2021), which empirically Sharīʿah-compliance carried out by providers does not significantly moderate the relationship between perceived value and benefits on e-payment perceptions, this is due to the element of difficulty in distinguishing between payment systems that use interest rates and others. Based on the postulated explanations, the hypotheses assumed are as follows:…”
Section: Element Of Mooring Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Aji et al (2020) state that the riba' that may be contained in e-money can create individual disinterest in adopting e-money technology to become a major obstacle to creating a cashless society in Indonesia. However, an interesting finding is stated by Garrouch (2021), which empirically Sharīʿah-compliance carried out by providers does not significantly moderate the relationship between perceived value and benefits on e-payment perceptions, this is due to the element of difficulty in distinguishing between payment systems that use interest rates and others. Based on the postulated explanations, the hypotheses assumed are as follows:…”
Section: Element Of Mooring Effectsmentioning
confidence: 98%
“…Furthermore, research that emphasizes the factor of religious commitment (RC) into this topic has not been carried out thoroughly, whereas the Muslim’s awareness on compliance to avoid forbidden practices in the financial transaction has consciously influenced their behavior (Fauzia et al , 2020; Aji et al , 2020). Some previous findings have tried to elaborate compliance and Islamic knowledge factor as moderating variable adoption and perception to electronic payment, Aji et al (2020) stated in his research that knowledge on riba significantly moderating Muslim’s e-wallet adoption in Indonesia, where other findings showed that Islamic compliance is insignificantly moderating benefit and value perceived with perception on e-payment (Garrouch, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Various researched have studied that a technology can be regarded as more user friendly while the technology is easy to adopt (Garrouch 2021). E-payment user friendly can increase customers' trust levels since it has higher usability to decrease the possibility of error, which is an important dimension while offering online financial services.…”
Section: E-payment User Friendlymentioning
confidence: 99%
“…Penelitian sebelumnya yang dilakukan oleh Alshurideh et al, (2021) menemukan bahwa perceived security, perceived privacy, perceived ease of use, trust serta perceived usefulness sebagai beberapa faktor yang mampu mendorong konsumen ataupun masyarakat di dalam menggunakan teknologi e-payment di Uni Emirat Arab. Sementara itu, penelitian lain yang dilakukan oleh Garrouch (2021) di Arab Saudi menemukan bahwa perceived e-shopping values serta e-payment benefits sebagai 2 faktor yang mampu meningkatkan intensi masyarakat di dalam menggunakan layanan e-payment. Berdasarkan hasil penelitian sebelumnya dari kedua studi ini, maka peneliti merasa bahwa dibutuhkan studi secara lebih lanjut di dalam menemukan faktor apa sajakah yang mampu mendorong intensi masyarakat Indonesia di dalam menggunakan layanan e-payment, mengingat bahwa kedua penelitian tersebut dilakukan terhadap masyarakat di wilayah Arab serta Timur Tengah yang kemungkinan besar memiliki perbedaan karakteristik serta sikap apabila dibandingkan dengan penduduk ataupun masyarakat yang tinggal di Indonesia.…”
Section: Pendahuluan Latar Belakangunclassified
“…Selain itu juga, berdasarkan hasil analisis data yang telah dilakukan, ditemukan juga bahwa selain benefits, trust serta ease of use juga ditemukan berpengaruh positif dan signifikan di dalam mempengaruhi intensi konsumen serta masyarakat Indonesia di dalam menggunakan berbagai layanan ataupun aplikasi e-payment yang tersedia. Hasil yang diperoleh pada penelitian ini pun sejalan dengan hasil studi sebelumnya yang dilakukan oleh Wilson (2019), Alshurideh et al, (2021) serta Garrouch (2021) yang juga menemukan pengaruh signifikan dan positif yang diberikan oleh benefits, trust serta ease of use terhadap intensi masyarakat untuk mengadopsi ataupun menggunakan suatu sistem, layanan ataupun teknologi baru yang dikembangkan oleh suatu perusahaan. Berdasarkan pada hasil analisis data yang diperoleh ini, maka dapat dipahami bahwa tingkat kepercayaan yang konsumen miliki terhadap perusahaan yang mengelola serta menciptakan aplikasi e-payment di Indonesia ini berperan penting dan signifikan di dalam menentukan sejauh mana konsumen akan mengadopsi ataupun menggunakan layanan e-payment yang tersedia.…”
Section: Pembahasanunclassified